Performance Analysis of Reliability-Based Decoding Algorithm for Short Block Length Turbo Codes. Issue 3 (4th May 2022) - Salija, P.; Yamuna, B.; Padmanabhan, T. R.; Mishra, Deepak
Abstract : Demand for transmission using short block length messages has been increased recently in applications including satellite communication, mobile communication, wireless sensor networks, and machine type communications. Unacceptable performance degradation associated with the short block length Turbo codes restricted its use for applications requiring communication with short block length codewords. A novel performance improved reliability-based decoding algorithm for short block length Turbo codes has been formulated and proposed by the authors. The proposed algorithm has a coding gain of 2.45 dB at a BER of 10 −3 over AWGN channel with BPSK modulation for a code rate of 1 4 . The algorithm has a channel adaptive complexity and has shown nearly 82% reduction in the decoding time complexity for the rate 1 4 Turbo code at 3 dB SNR. As an extension of this earlier work, a detailed performance analysis of the algorithm on different Turbo codes has been carried out. A four-state Turbo encoder has been used to bring out the key aspects of the level based algorithm which is driven by reliability as the key parameter. The formulated algorithm has been applied to different Turbo encoder structures namely 3GPP LTE and CCSDS Turbo codes and a detailed analysis has been carried out in this paper. Simulation results show a significant improvement in the error correction performance of short block length Turbo codes. The algorithm also leads to a marked improvement in time complexity at high SNRs. The algorithm is an attractive solution for applications requiring communication with short block lengths.